Miniature landscapes - Diaconu, Madalina (Aesthetica Preprint, 2024)
The concept of miniature landscapes is used in this paper for human-made, three-dimensional landscape at reduced scale. Their diversity ranges from Japanese gardens to indoor habitats and from scientific and artistic dioramas to mini-railroad-systems and snow globes. Many of them employ mixed media and combine natural with artificial items. Depending on their genre, context and addressee, micro-landscapes critically reflect on the naturalization of vision in science, replicate cosmogenesis at small scale, satisfy biophilia, fascinate for their skillful reproduction of details and nostalgically recall childhood pleasures. The enjoyment of making and watching them can be explained in terms of functional beauty and interplay of scales; moreover, miniature landscapes “trap” the outer world in capsules, creating a domestic sublime, and activate attention and imagination.